2014
DOI: 10.1039/c3cp53683a
|View full text |Cite
|
Sign up to set email alerts
|

Probing the electronic and geometric structure of ferric and ferrous myoglobins in physiological solutions by Fe K-edge absorption spectroscopy

Abstract: We present an iron K-edge X-ray absorption study of carboxymyoglobin (MbCO), nitrosylmyoglobin (MbNO), oxymyoglobin (MbO 2 ), cyanomyoglobin (MbCN), aquomet myoglobin (metMb) and unligated myoglobin (deoxyMb) in physiological media. The analysis of the XANES region is performed using the full-multiple scattering formalism, implemented within the MXAN package. This reveals trends within the heme structure, absent from previous crystallographic and X-ray absorption analysis. In particular, the iron-nitrogen bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 129 publications
(209 reference statements)
10
50
0
Order By: Relevance
“…Adopting such an approach, X-ray scattering studies of MbCO in solution with a 100-ps resolution were recently reported (38)(39)(40), but the spatial resolution is such that tertiary and global structural changes can be probed but not atomic-scale changes. In addition, this approach does not deliver information about the electronic structure of the active site, which plays a central role in the biochemistry and reactivity of heme proteins (41,42). The valence 3d electrons of the iron atom are significantly delocalized over the porphyrin ligand π*-orbitals, and the ability of the heme to redistribute charge and spin density plays an important role in the formation and stabilization of a variety of intermediates important for biological function (42)(43)(44).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Adopting such an approach, X-ray scattering studies of MbCO in solution with a 100-ps resolution were recently reported (38)(39)(40), but the spatial resolution is such that tertiary and global structural changes can be probed but not atomic-scale changes. In addition, this approach does not deliver information about the electronic structure of the active site, which plays a central role in the biochemistry and reactivity of heme proteins (41,42). The valence 3d electrons of the iron atom are significantly delocalized over the porphyrin ligand π*-orbitals, and the ability of the heme to redistribute charge and spin density plays an important role in the formation and stabilization of a variety of intermediates important for biological function (42)(43)(44).…”
Section: Significancementioning
confidence: 99%
“…In addition, this approach does not deliver information about the electronic structure of the active site, which plays a central role in the biochemistry and reactivity of heme proteins (41,42). The valence 3d electrons of the iron atom are significantly delocalized over the porphyrin ligand π*-orbitals, and the ability of the heme to redistribute charge and spin density plays an important role in the formation and stabilization of a variety of intermediates important for biological function (42)(43)(44). Time-resolved X-ray absorption spectroscopy (XAS) (45) offers the advantage of interrogating the electronic and geometric structure of the biochemically active center of the system with elemental selectivity (i.e., the Fe atom).…”
Section: Significancementioning
confidence: 99%
“…[1,3] Another alternative is the presence of a strongly binding ligand, e.g., the metal-oxo groups proposed to be the reactive species in many enzymatic and synthetic systems. [4][5][6][7] Oxo groups also appear as bridging ligands in many bi-and multinuclear transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The K preedge directly probes the unoccupied and partially occupied valence orbitals involved in catalysis and can play a key role in the identification and characterization of reactive sites, e.g., site symmetry, oxidation state and ligand-field splitting. [6][7][8][9][10] Westre and co-workers analyzed the iron K pre-edges for a large series of systems, both experimentally and theoretically. They showed how energy and intensity depend on oxidation state and coordination number, and provided a general method for their interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…They showed how energy and intensity depend on oxidation state and coordination number, and provided a general method for their interpretation. 7 The K pre-edge has already been very useful in geometry and electronic structure analysis, such as determining the protonation state of a ferryl intermediate 9 and the coordination number of a non-heme iron active site. 10 For centrosymmetric complexes, the K pre-edges are asso- ciated with electron transitions from the 1s to the 3d orbitals.…”
Section: Introductionmentioning
confidence: 99%